Mural as a multicultural media and paradigm for elementary school teacher education students - Setyaningrum, Fery; Faozata Adzkia , Sagaf; Probosiwi , Probosiwi (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2024)
Indonesia is a country with diverse cultures, ethnicities, races, religions, and all kinds of differences. Seeing the unique characteristics of Indonesian society, full of multicultural, it is very interesting to look at the learning process. It can be seen that the nation's generation comes from young people, of course through education they can be given an understanding of differences. Murals can be used as an educational medium. The aim of this research is to analyze murals as a media and multicultural paradigm for PGSD students. This research method uses a qualitative research type. Using data collection techniques of observation, interviews, and document review. Data analysis uses data reduction, data verification, and drawing conclusions. The research results show that murals are a type of fine arts education that can be used as a medium for the process of transferring knowledge to students. Through art murals, students can process their feelings by expressing themselves and refreshing themselves as well as becoming aware of various social problems. Apart from that, murals can also be useful for exploring local wisdom as one's own cultural potential, apart from honing oneself to understand the meaning of the value of mutual cooperation education. Apart from that, the mural paradigm can be seen through mural learning based on cultural pluralism and cultural diversity. The gap in this research is that murals are usually only used as expressions of artistic creation, even murals on the streets also give the impression of vandalism. However, apart from that, murals have the value of conveying a certain meaning in each work.